Energic metabolism studies in pediatric cancer patients - M. V. Konovalova; A. Yu. Vashura; D. V. Litvinov; E. V. Skorobogatova; N. E. Filippova; S. V. Belmer; G. Ya. Tseitlin (Медицинский вестник Юга России, 2010)
The aim. To estimate heat capacity (C) measurements for individual dietary support of pediatric cancer patients during chemotherapy. Material and methods. 43 cancer children are examined. Group 1: 15 children, 5 children receiving polychemotherapy, 10 children – in post-BMT period (5 of them were re-examined on clinical indications). Thus we got 21 resting heat capacity measures. Group 2 includes 14 children with cancer after completing chemotherapy. Group 3 (control group) – 14 children with gastroenterological pathology. (C) is determined by indirect calorimetry, then basal metabolic rate (BMR) is calculated by formula BMR=90%C and compared with (Cf), calculated by formula WHO (1985). The results. In group 1 the average values of BMR and Еоф considerably differ: 986,5 and 1285,9 kcal accordingly (p<0,05). In group 2 BMR value is lower than Cf, however the difference is inconsiderable. The amount of children with decreased BMR in group 1 is considerably higher than in groups 2 and 3 – 76,2%; 42,9% and 28,6% accordingly (p<0,05). On the contrary group 3 includes more children with increased BMR, than group 1 (p<0,01). The marked decrease of heat capacity (C decrease) in group 1 is mainly associated with toxic effects of polychemotherapy and BMT on metabolic processes. Conclusion. The findings justify the need to monitor the pediatric cancer patients during special treatment to estimate their heat capacity to work out individual programs of dietary support with further assessment of effectiveness and correction.